Zanos in trpljenje Alije Đerzeleza - Dukić, Davor (Slavistična revija, 2020)
The article examines the value charge of the main character in Ivo Andrić's short story "The Journey of Ali Djerzelez" (1920). The analysis of intratextual evaluation in the short story at the levels of direct (essential) and indirect (situational) evaluation, as well as of evaluation in the domain of the implied author is conducted based on the pioneering study of Simone Winko (1991) on axiological textual analysis and using Wayne Booth's (1961) concept of the "implied author" and certain narratological terms of Wolf Schmid (2005). Ultimately, final insights of axiological interpretation are compared with some of the earlier interpretive insights into Andrić's short story.
Keywords: aksiološka analiza; Andrić, Ivo; besedilne analize; implicitni avtor; vrednote; vrednotenje